KONSTRUKSI SOSIAL MEDIA MASSA ATAS HUBUNGAN INDONESIA-MALAYSIA DAN PENGARUHNYA TERHADAP NETWAR-TAUNTWAR - Ruli Inayah Ramadhoan (The Indonesian Islamic Studies and International Relations Association (Insiera), 2020)
History of Indonesia’s confrontation towards Malaysia in 1963 left a strong impression within Indonesian as well as Malaysian society. It was the term ‘Ganyang Malaysia’ that was depicted as a symbol of protest from Indonesia was well acknowledged by the society. In the development of the issue to the present days, the term that is considered heart-breaking for Malaysian society is continuously used by Indonesian as ‘blasphemy’ towards Malaysian. As a response, Malaysian called ‘Indon’ to address the people of Indonesia. Indonesian were not accepting the term ‘Indon’ that is used to address them since it tends as an insult. When hike of political tension between Malaysia and Indonesia occured, media has often used the idioms in their headlines and news contents repeatedly. This research covers the practice of the social-political construction of mass media in ASEAN taking an example of the news reported in Indonesia and Malaysia. Media constructions of Indonesia-Malaysia’s conflict produced the negative stigma of both states which resulted in the negative image of Indonesian society in Malaysia and vis-à-vis. The image constructed, then spreads to the public and spread around the internet which resulted in commotion. The spirit of anti-Malaysia and the spirit of anti-Indonesia in the virtual realm is the potential sources of conflicts in the future. It will hamper ASEAN collective efforts in developing an awareness of united ASEAN society.